2014
DOI: 10.1016/j.jaut.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Compromised central tolerance of ICA69 induces multiple organ autoimmunity

Abstract: For reasons not fully understood, patients with an organ-specific autoimmune disease have increased risks of developing autoimmune responses against other organs/tissues. We identified ICA69, a known β-cell autoantigen in Type 1 diabetes, as a potential common target in multi-organ autoimmunity. NOD mice immunized with ICA69 polypeptides exhibited exacerbated inflammation not only in the islets, but also in the salivary glands. To further investigate ICA69 autoimmunity, two genetically modified mouse lines wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…Interestingly, analysis of our patient cohort revealed that RRMS patients display an enhanced TCR repertoire diversity as illustrated by increased numbers of unique clones and an increased sample overlap. Our findings support pilot data from de Paula Alves Sousa and coworkers (43) in a small cohort of five RRMS patients and together suggest that in MS there is a perturbation of clonal elimination, potentially caused by an impaired deletion of autoreactive clones (44)(45)(46)(47). It would be of interest to obtain more information about the TCR repertoire in the target organ, i.e.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, analysis of our patient cohort revealed that RRMS patients display an enhanced TCR repertoire diversity as illustrated by increased numbers of unique clones and an increased sample overlap. Our findings support pilot data from de Paula Alves Sousa and coworkers (43) in a small cohort of five RRMS patients and together suggest that in MS there is a perturbation of clonal elimination, potentially caused by an impaired deletion of autoreactive clones (44)(45)(46)(47). It would be of interest to obtain more information about the TCR repertoire in the target organ, i.e.…”
Section: Discussionsupporting
confidence: 90%
“…PBMCs were loaded with a pool of peptides each 10 µg/ml (MBP 85-99 , MOG 222-241 , PLP [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] , PLP 129-148 , MOG 97-serum. IL-2 (20 U/ml) was added on days 4, 7, and 10.…”
Section: Determination Of Myelin-specific Frequencies Of Human T Cellsmentioning
confidence: 99%
“…To investigate ICA69 autoimmunity (Bonner et al, 2012; Pietropaolo et al, 1993), in an elegant recent study two genetically modified mouse lines were generated to modulate thymic ICA69 expression: the heterozygous ICA69del/wt line and the thymic medullary epithelial cell-specific deletion Aire-ΔICA69 line (Fan et al, 2014). Suboptimal central negative selection of ICA69-reactive T-cells was observed in both lines.…”
Section: Genetic Susceptibilitymentioning
confidence: 99%
“…To examine the function of the TEC/EAK aggregates in vivo , collect the TEC/EAK hydrogel after O/N culture and transplant under the kidney capsule of an athymic nude mouse, using previously described procedure 11,14 .…”
Section: Protocolmentioning
confidence: 99%